Reflections: Cutting-Edge Citizen Science in the Desert and at a Museum - Silka, Linda (Maine Policy Review, 2017)
Linda Silka examines the University of Arizona’s Project Harvest, led by Mónica Ramirez-Andreotta, and the Denver Museum of Nature & Science’s Genetics of Taste Lab led by Nicole Garneau.
Keywords: citizen science